A retrospective study of 370 patients with oral lichen planus in Turkey - (:unkn) unknown (MEDICINA ORAL S L, 2013)
Objectives: Although several detailed studies concerning the patient profile and clinical features of oral lichen planus have been undertaken all over the world in different populations, a similar study has not yet been conducted in a Turkish population. The purpose of this retrospective study was to describe the demographic and clinical characteristics of a group of patients with oral lichen planus in Turkey. Study Design: Charts of 370 patients, from the archive of Oral Diagnosis and Radiology Department of Marmara University Faculty of Dentistry (Istanbul, Turkey), with histologically confirmed clinical diagnosis of oral lichen planus in the period 1990-2010 were retrospectively reviewed. Results: Of the 370 patients, 260 (70.3%) were women and 110 (29.7%) were men. The mean age was 49.84 +/- 13.41 years (range of 16-83). The lesions were asymptomatic in 63 patients (17%). Nearly half of the patients (47.6%) had multiple sites of involvement. Predominantly red forms were the most frequent, affecting 60.5% of patients. Approximately 17% of the patients had symptoms of possible extraoral involvement. No evidence suggesting a connection between oral lichen planus and tobacco or alcohol use was found. Only one out of the 370 cases had histologically proven malignant transformation. Conclusions: The patient profile and clinical features of oral lichen planus in Turkey were generally similar to those described in other populations. The preponderance of the red forms and also the fact that majority of patients referred themselves to our clinic highlighted the lack of awareness among Turkish health care providers about lichen planus.
Keywords: Oral lichen planus; clinical features; patient profile; MANAGEMENT